Epidemiological, Clinical and Microbiological Characteristics of Patients with Bloodstream Infections Due to Carbapenem-Resistant K. Pneumoniae in Southern Italy: A Multicentre Study - Lorenzo Onorato; Bruno Sarnelli; Federica D'Agostino; Giuseppe Signoriello; Ugo Trama; Angelo D'Argenzio; Maria Vittoria Montemurro; Nicola Coppola (MDPI AG, 2022)
Background: In the present study, our aim was to evaluate the clinical and microbiological characteristics of a cohort of patients with bloodstream infections (BSI) due to Carbapenem-Resistant Enterobacteriaceae (CRE) and investigate the independent predictors of mortality. Methods: All episodes of carbapenem-resistant E. coli (CREc) or K. pneumoniae (CRKp) BSI that were subject to a mandatory notification from January to December 2020 in all acute care hospitals and long-term care facilities of the Campania region in southern Italy were enrolled. All carbapenem-resistant strains were assessed through molecular tests for the presence of five carbapenemase gene families, i.e., K. pneumoniae Carbapenemase (KPC), oxacillinase-48 (OXA-48), New Delhi Metallo-β-lactamase (NDM), Verona integron encoded metallo-β-lactamase (VIM) and Imipenemase (IMP). Results: During the study period, a total of 154 consecutive non-repeated CRE BSI, all due to CRKp, were reported. The most frequently identified genes were KPC in 108 cases (70.1%), followed by metallo-betalactamases (MBL) (16.2%), and OXA-48 (2.6%); in 17 isolates (11%) no carbapenemase was detected. The overall mortality at 90 days was 41.9%. Using a log-rank test, patients without risk factors for CRE infections showed a significantly lower cumulative mortality (p = 0.001). After multivariate logistic regression analysis, the presence of at least one risk factor was the only predictor of mortality (OR: 1.7, 95% CI 1.2-6.1, p = 0.015). Conclusions. The study reported a non-negligible prevalence of MBL-producing organisms among CRKp isolated from blood cultures in our region. This data highlights the importance of molecular characterization of all clinical isolates of carbapenem-resistant organisms.